2021
DOI: 10.3855/jidc.13962
|View full text |Cite
|
Sign up to set email alerts
|

A 10-year retrospective comparative analysis of the clinical features of brucellosis in children and adults

Abstract: Introduction: Brucellosis is a zoonosis with a wide spectrum of clinical manifestations. However, it is still unclear whether the clinical manifestations in children are significantly different from those in adults. Methodology: Patients with brucellosis and treated at the General Hospital of Ningxia Medical University between 2009 and 2019 were divided into two groups; children (88) and adults (354). Thereafter, the records of the two groups were analyzed retrospectively. Results: The findings sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…The authors demonstrated that fever was the most comon symptom in both children and adults (82.9% vs 61.5%, respectively), followed by joint pain, fatigue, anorexia and low back pain. 10 In our study, as reported in previous studies, the most common symptoms were arthralgia and fever and the most common physical examination findings were hepatomegaly and arthritis.…”
Section: Brusellosis In Pediatric Patients May Have a Wide Variety Of...supporting
confidence: 84%
See 3 more Smart Citations
“…The authors demonstrated that fever was the most comon symptom in both children and adults (82.9% vs 61.5%, respectively), followed by joint pain, fatigue, anorexia and low back pain. 10 In our study, as reported in previous studies, the most common symptoms were arthralgia and fever and the most common physical examination findings were hepatomegaly and arthritis.…”
Section: Brusellosis In Pediatric Patients May Have a Wide Variety Of...supporting
confidence: 84%
“…9 It has been reported that brucellosis often affects children aged 5 to 15 years of age in different pediatric studies. 1,10,11 A study conducted on 496 children with brucellosis in Eastern Turkey, showed that patients' age ranged from 1-16 years with a mean age of 10.0±3.95 years. Half of the children were over 10 years of age and the male/female ratio was 1.5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 18 studies conducted in our country in 2011 and after, in which children aged <18 years were evaluated, the mean age ranged between 7.3-11.9 years (Table 2) [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. In the reports, male case rates are generally between 30-69.3% [25][26][27], in our country, apart from 3 studies reporting this rate as 45-46.8% [10,11,17], male predominance is observed with a rate of 54.4-75% in 15 studies (Table 2) [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%